ANALISIS PENGARUH E-COMMERCE, PROMOSI, FINANCIAL LITERACY, DAN LIFESTYLE HEDONIS TERHADAP PERILAKU KONSUMTIF MAHASISWA AKUNTANSI - Maryam, Ilmatul; Novi Darmayanti; Dewi Kusmayasari (E-Jurnal Akuntansi TSM, 2025)
This research aims to analyze the influence of E-commerce, Promotion, Financial Literacy, and Hedonic Lifestyle on the Consumptive Behavior of accounting students at Universitas Kabupaten Lamongan and Universitas Nahdlatul Ulama Surabaya. The method used in this study is quantitative with primary data. Data collection techniques were carried out by distributing questionnaires. The number of respondents in this study was 135 respondents. The data were analyzed using the smartPLS 4 software. Based on the research results, there is a positive and significant influence of E-commerce on Consumptive Behavior. Promotion does not have a significant effect on Consumptive Behavior. Financial Literacy has a positive and significant effect on Consumptive Behavior. Hedonic Lifestyle has a positive and significant effect on Consumptive Behavior. This research can be a source of information related to the variables that influence consumptive behavior. Furthermore other approaches can be used to further explore the motivations for consumer behavior. This research includes promotion as an additional independent variable influencing consumer behavior, allowing for further research.